Penerapan Model Pembelajaran Treffinger Pada Pembelajaran Geografi - Nurjannah, Humairah; Saputro, Alief; Maddatuang, Maddatuang; Fikri, Muh Jibran Nidhal (LaGeografia, 2020)
This study aims to determine whether the application of the Treffinger learning model can improve student learning outcomes in geography learning in class X SMA 7 Sinjai.  This research method uses pretest posttest control group design experimental research.  The subjects in this study were two classes of IPS X in SMA Negeri 7 Sinjai namely X IPS 1 and X IPS 2. The data analysis technique in the study used SPSS 22 for windows.  For the hypothesis test the t-test (independent samples t test) is used.  The results showed that the Treffinger model affected the learning outcomes in learning geography of class X IPS students of SMA Negeri 7 Sinjai.  This shows Ho was rejected and Hi was accepted.  The gain score of students' learning outcomes using the Treffinger model is better (8.97) than students who do not use the model (1.41).  Suggestions for teachers, the use of this learning model can be done as an alternative model to improve student learning outcomes.  Further research is also recommended to: a) test the effect of applying the Treffinger learning model to other variables and to locations, levels of education, or other material;  and b) integrate or compare with other learning models to be used as alternative learning models in schools.  Quasi (Quasi Experiment) with design.